Zen: the religion of the Samurai : a study of Zen philosophy and discipline in China and Japan - Nukariya, Kaiten (Floating Press, 2009)
Interested in learning more about the Zen tradition? Skip the watered-down, touchy-feely translations that crowd the shelves of most Western bookstores and go straight to the source with this rigorous treatment of the subject. Author Kaiten Nukariya offers a compelling overview of Zen within its proper historical and cultural context. A must-read for those interested in history, comparative religious studies, and world cultures